(untitled) (Revista de Artes Marciales Asiáticas, 2025)
This study aimed to deeply examine how the Guangdong Chin Woo Athletic Association, within the specific historical and regional context of Republican Era China, shaped members’ bodily concepts, behavior patterns, and values through its unique system of bodily discipline. It examines the intricate relationships between this process and individual identity, group identification, and national identity. This paper applies Foucault’s theory of bodily discipline to address the lack of previous research on the bodily disciplinary practices of specific regional Chin Woo branches and their sociocultural implications. Based on a meticulous review and analysis of primary archival materials, including the works Jing Wu Ben Ji and Jing Wu Yue Chuan, this study systematically analyzes the diverse bodily disciplinary practices of the Guangdong Chin Woo Athletic Association, encompassing the modernization of Chinese martial arts training, the organization of diverse cultural activities, and the establishment of strict institutional norms. The research reveals that the bodily discipline of the Guangdong Chin Woo Athletic Association was not merely a simple physical skills training, but a complex social process that integrated the call of the times, the leadership and promotion of social elites, organizational operational guarantees, and cultural inheritance and innovation. This disciplinary system effectively internalized specific bodily standards, behavioral norms, and values into members’ daily practices, not only enhancing members’ self-confidence and sense of group belonging but, more importantly, closely linking individual bodily experiences with national cultural identity and national identity, making the body a symbol carrying the hope of national rejuvenation. The study concludes that the bodily discipline of the Guangdong Chin Woo Athletic Association is a vivid embodiment of Modern China’s sports modernization transformation, bodily cultural changes, and the intertwining of power, identity construction, and social mobilization. It profoundly reveals the historical process in which the body was discovered, disciplined, and endowed with symbolic meaning under specific historical conditions.